Workload on SOEs employee performance: Mediating effects of work stress and burnout - Meliani, Azzalia; Heriyadi, Heriyadi; Rosnani, Titik; Saputra, Pramana (Journal of Management and Digital Business, 2024)
Sakernas August 2023 results also show that the quality of workers in West Kalimantan is low. State-owned enterprises (SOEs) in West Kalimantan are vulnerable to high workloads. Employees often encounter diverse pressures and challenges in performing their responsibilities, including time constraints, heavy workloads, and rising performance expectations. This study aims to analyze the impact of workload on employee performance in state-owned enterprises (SOEs) in West Kalimantan, emphasizing the mediating roles of work stress and burnout. The study includes a sample of 145 respondents and utilizes Structural Equation Modeling (SEM) and Partial Least Squares (PLS). The research findings indicate that workload hurts employee performance but positively affects work stress and burnout. Work stress positively affects burnout but does not affect employee performance. Burnout hurts employee performance. Workload through work stress does not affect employee performance but hurts employee performance through burnout. Work stress hurts employee performance through burnout.